Exploring the possibility of applying the GOMS model to e-banking software design - Baftiu, Naim; Mjaku, Malush (Technium Social Sciences Journal, 2021)
The GOMS model in human-computer interaction could be applied in improving software design in e-banking, ie in improving the function of appointed bank clients as outermost users of software. We researched users' opinions on some actions performed in the software and on suggestions for making changes to the software. An online survey questionnaire was used as a research instrument. The analysis of the survey results answered the question of whether the application of the GOMS model in the design software for e-banking can be significantly improved. There were also proposals to introduce changes that would improve the function of software intended for furthermost users.